(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The aim of this paper is to introduce the notions of the length and the mean of an interval-valued fuzzy structure in Sheffer stroke Hilbert algebras. The notions of length-fuzzy subalgebras and mean-fuzzy subalgebras of Sheffer stroke Hilbert algebras are introduced, and related properties are investigated. Characterizations of length-fuzzy subalgebras and mean-fuzzy subalgebras are discussed. Relations between length-fuzzy subalgebras (resp., mean-fuzzy subalgebras) and subalgebras are established. Moreover, we discuss the relationships among length-fuzzy subalgebras (resp., mean-fuzzy subalgebras) and upper and lower-level subsets of the length (resp., mean) of an interval-valued fuzzy structure in Sheffer stroke Hilbert algebras.